Novel porous β-cyclodextrin/pillar[5]arene copolymer for rapid removal of organic pollutants from water. (15th July 2019) - Lu, Pengpeng; Cheng, Jincheng; Li, Yifan; Li, Li; Wang, Qiang; He, Chiyang
Highlights: A novel β -cyclodextrin/pillar[5]arene copolymer has been prepared. It has good water immersibility and large BET surface area. It shows high adsorption capacity, fast binding kinetics and good reusability. It presents rapid removal ability for various organic pollutants. Abstract: A novel porous β ‐cyclodextrin/pillar[5]arene copolymer was prepared using tetrafluoroterephthalonitrile as cross-linker for rapid removal of variety of organic pollutants. The copolymer was characterized by water contact angle, scanning electron microscope, FT-IR spectrum, solid-state 13 C NMR spectrum, thermo-gravimetric analysis, nitrogen adsorption-desorption isotherms, and elemental analysis. Results showed that the co-polymer had good water immersibility, co-existing micro-/meso-pores, and a large specific surface area (BET) of 479 m 2 /g. The copolymer presented high adsorption capacity with the maximum adsorption capacity of 258 mg/g for bisphenol A and good reusability and reproducibility. It also showed fast binding kinetics with the apparent second-order rate constants of 0.109−0.179 g/mg·min and simultaneously rapid removal ability with removal efficiencies of 74–90% within 30 s for variety of organic pollutants. The new copolymer can be potentially used as adsorbent for rapidly removing a wide range of organic pollutants in wastewater.